Initial Patient Assessment Workshop - John Mahoney (Association of American Medical Colleges, 2010)
Abstract Introduction In a small-group workshop setting, medical students work with a clinical facilitator on eight basic clinical scenarios. The intention is to guide learners through how they would approach initial assessment of a patient and to help them begin to think like a clinician who is going to make a contribution to the clinical care of the patient. The case scenarios provide a vehicle to launch a fast-paced discussion of how students could begin to deal with common, acute, or time-sensitive clinical conditions. This workshop is intended to be taught immediately before the start of core clinical clerkships. Methods Groups of eight students and one facilitator work through eight clinical scenarios over 75 minutes. Three basic questions form a framework for the discussion: What's likely to be wrong? What to do? and What will a physician possibly or likely order, even before arriving at the scene? Each case is defined by only one to three lines of text, leaving a great deal to be considered in the small-group discussion of these ill-defined scenarios. The case discussion begins with reading the statement of the presenting scenario. The facilitator then helps the group work through the three basic questions. Results In general, this workshop has been highly successful as measured by student evaluations and faculty observations. Students quickly embraced the case scenarios and participated with energy and enthusiasm. The overall workshop was very well received, and highly rated on student evaluations and comments (72% to 88% excellent or good across three class years of students). All surveyed rated the session as one to include in next year's course. This workshop has also been presented to other class-years of students at the end of the second-year medical school curriculum, within a clinical procedures course. These learners rated this workshop highly as well. Discussion This point in students' training is a unique teachable moment that is often characterized by both excitement and trepidation about assuming clinical responsibilities. These scenarios are constructed to be level-appropriate for a student who is just about to embark on their in-depth clerkship experiences. These cases provide an important opportunity to help students move from the classroom environment where any patient discussion is merely an academic exercise, to the bedside, where it is likely necessary to think more practically and potentially begin treatment even before a patient has been fully assessed.